A strategy towards melanin-based functional material: rGO and sulfonated melanin composites - Bregadiolli, Bruna Andressa [UNESP]; Paulin, João Vitor; Albano, Luiz Gustavo Simão [UNESP]; Martins, Lucas Michelão [UNESP]; Camargo, Davi Henrique Starnini de; Silva-Filho, Luiz Carlos da [UNESP]; Bufon, Carlos Cesar Bof; Graeff, Carlos Frederico de Oliveira [UNESP] (Royal Society of Chemistry, 2021)
Melanin is a natural pigment and one of the most promising materials for the emerging field of bioelectronics. The low conductivity of this class of materials is a limiting factor to their implementation on electronics. In this work, we have improved the electrical properties of a melanin-like material by combining it with reduced graphene oxide (rGO). Three different concentrations of rGO (5, 10 and 15 wt%) were studied. The composites were structurally (SEM, Raman, XPS, FTIR, and solid-state NMR) and optically (UV-vis and PL) characterized. The electrical properties were investigated through transient current, current-voltage curves and electrochemical impedance under different humidity levels. An improved DC conductivity was found for the 15%rGO@sulfonated melanin composite. The results suggest that, together with sulfonated melanin, it could potentially be suitable for application in bioelectronics and/or organic electronics
Uma estratégia para a obtenção de um material funcional baseado em melanina: compósitos de melanina sulfonada e rGO
Keywords: Bioeletronic material; Melanin; rGO; Composites; Electrical Properties